Preferences for childcare policies: Theory and evidence - Rainald Borck; Katharina Wrohlich (Verein für Socialpolitik, 2010)
We analyse preferences for public, private or mixed provision of childcare theoretically and empirically. We model childcare as a publicly provided private good. Richer households should prefer private provision to either pure public or mixed provision. If public provision redistributes from rich to poor, the rich should favour mixed over pure public provision, but if public provision redistributes from poor to rich, the rich and poor might favour mixed provision while the middle class favour public provision ('ends against the middle'). Using estimates for household preferences from survey data, we find no support for the ends-against-the-middle result.
Keywords: D72; H42; J13; 330; childcare; redistribution; political preferences; public provision of private goods